Rationally Designed Peptides and Peptidomimetics as Inhibitors of Amyloid‑β (Aβ) Aggregation: Potential Therapeutics of Alzheimer’s Disease - Goyal, Deepti; Shuaib, Suniba; Mann, Sukhmani; Goyal, Bhupesh (ACS combinatorial science, 2017)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease with no clinically accepted treatment to cure or halt its progression. The worldwide effort to develop peptide-based inhibitors of amyloid-β (Aβ) aggregation can be considered an unplanned combinatorial experiment. An understanding of what has been done and achieved may advance our understanding of AD pathology and the discovery of effective therapeutic agents. We review here the history of such peptide-based inhibitors, including those based on the Aβ sequence and those not derived from that sequence, containing both natural and unnatural amino acid building blocks. Peptide-based aggregation inhibitors hold significant promise for future AD therapy owing to their high selectivity, effectiveness, low toxicity, good tolerance, low accumulation in tissues, high chemical and biological diversity, possibility of rational design, and highly developed methods for analyzing their mode of action, proteolytic stability (modified peptides), and blood–brain barrier (BBB) permeability.